2021
DOI: 10.1111/jfb.14975
|View full text |Cite
|
Sign up to set email alerts
|

On the invalid resurrection of the lamprey genus Exomegas Gill, 1883

Abstract: The lamprey genus Exomegas Gill, 1883, was erected on the assumption that it was distinguishable from Geotria Gray, 1851, by possessing three rather than two cusps on the transverse lingual lamina (TLL). Based on literature review and examination of holotypes and new data, the authors reaffirm that the TLL of Geotria possesses two or three cusps in the adult stage. The reduction or disappearance of the middle cusp at the beginning or during the spawning run constitutes a key feature of Geotria. The resurrectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…There are four species of anadromous parasitic lamprey in the southern hemisphere, including the pouched lamprey Geotria australis, previously considered to be the only member of its family (Geotriidae), which appeared to have a very wide spawning distribution; rivers south of 32°S in Australia (including Tasmania), New Zealand, Chile and Argentina (Neira et al 1988). However, environmental DNA (eDNA), and molecular and morphological studies have revealed a cryptic taxon in Argentina, revalidating the original description in 1868 of the Patagonian (or Argentinian pouched) lamprey G. macrostoma (Nardi et al 2020;Riva-Rossi et al 2020;Baker et al 2021, Riva-Rossi et al 2022). This corroborates studies indicating that Geotria populations in Argentina, Chile and Australasia are morphologically distinct (Neira et al 1988), and is in accordance with the suggestion by Potter et al (1979) that, following the direction of the prevailing currents, young adults from Argentina should move south and east in their marine phase, and those from Chile should move north.…”
Section: Introductionmentioning
confidence: 99%
“…There are four species of anadromous parasitic lamprey in the southern hemisphere, including the pouched lamprey Geotria australis, previously considered to be the only member of its family (Geotriidae), which appeared to have a very wide spawning distribution; rivers south of 32°S in Australia (including Tasmania), New Zealand, Chile and Argentina (Neira et al 1988). However, environmental DNA (eDNA), and molecular and morphological studies have revealed a cryptic taxon in Argentina, revalidating the original description in 1868 of the Patagonian (or Argentinian pouched) lamprey G. macrostoma (Nardi et al 2020;Riva-Rossi et al 2020;Baker et al 2021, Riva-Rossi et al 2022). This corroborates studies indicating that Geotria populations in Argentina, Chile and Australasia are morphologically distinct (Neira et al 1988), and is in accordance with the suggestion by Potter et al (1979) that, following the direction of the prevailing currents, young adults from Argentina should move south and east in their marine phase, and those from Chile should move north.…”
Section: Introductionmentioning
confidence: 99%
“…It thus elevated Geotria macrostoma f. gallegensis Smitt, 1901, to the species rank without providing distinguishing diagnostic characters. The proposal of Firpo Lacoste et al (2021) to allocate lampreys from Argentina under Exomegas was subsequently refuted by Riva Rossi et al (2022), who clearly demonstrated that the three TLL cups were reduced to two during adult life, which is a key a diagnostic character of Geotria .…”
Section: Introductionmentioning
confidence: 99%